(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
Higher education digital in their works technologies education based on The organization of processes, increasing the competence of future specialists in working with digital technologies in the educational process is a pressing issue. The article presents educational considerations for preparing future teachers of technological education for project activities based on digital technologies.